INCREASING OF EFFICIENCY OF THE COOPERATION OF RESCUE COMPONENTS OF THE INTEGRATED RESCUE SYSTEM OF THE SR IN THE CONTEXT OF EDUCATION - Kováčová, Lucia; Boguská, Danka; Mesároš, Marián (International Multidisciplinary Scientific GeoConference SGEM, 2018)
The objective of this article is to determine the need for joint security education of rescue components of the Slovak Integrated Rescue System. The reason for that is the absence of the joint education of these units which represents a critical point of their cooperation. In the introductory part we focused on the IRS's characteristics as well as description of the security education. An important part of this article is an analysis of the management process, coordination and cooperation of the rescue components, followed by a specification of critical points in their cooperation. As a result, we determined the need for the joint security education of the rescue components of the Slovak IRS, which we consider to be a significant factor for increasing the cooperation effectiveness.